Sustainable Community Development - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document explores the idea of sustainable community development and what this type of development can do to improve the quality of life within communities. This document examines what sustainable development entails and provides examples of the threats to quality of life that traditional approaches to development can generate. This document outlines six steps to a more sustainable approach to community development. This document is FCS7213-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.